Attainment Discrepancy and New Geographic Market Entry: The Moderating Roles of Vertical Pay Disparity and Horizontal Pay Dispersion. (19th December 2018) - Lim, Elizabeth
Abstract: Studies in the behavioural strategy literature have examined the influence of attainment discrepancy on new geographic market entry with inconclusive results. We clarified the relationship between attainment discrepancy and new geographic market entry by considering the moderating effects of managerial pay gaps with concentration on vertical pay disparity and horizontal pay dispersion. The framework also contributes to our understanding of tournament theory and social comparison theory by identifying specified performance contexts under which types of pay gaps conform to or violate theoretical predictions. Empirical analyses based on a panel data of Standard and Poor's (S&P) 500 firms from 1996 to 2006 showed that our hypotheses are largely supported.